Development of the Translating Allied Health Knowledge (TAHK) Framework - Hitch, Danielle (Int J Health Policy Manag, 2019)
Background: While evidence-based practice is a familiar concept to allied health clinicians, knowledge translation (KT) is less well known and understood. The need for a framework that enables allied health clinicians to access and engage with KT was identified. The aim of this paper is to describe the development of the Translating Allied Health Knowledge (TAHK) Framework. Methods: An iterative and collaborative process involving clinician and academic knowledge partners was utilised to develop the TAHK Framework. Multiple methods were utilised during this process, including a systematic literature review, steering committee consultation, mixed methods survey, benchmarking and measurement property analysis. Results: The TAHK Framework has now been finalised, and is described in detail. The framework is structured around four domains – Doing Knowledge Translation, Social Capital for Knowledge Translation, Sustaining Knowledge Translation and Inclusive Knowledge Translation – under which 14 factors known to influence allied health KT are classified. The formulation of the framework to date has laid a rigorous foundation for further developments, including clinician support and outcome measurement. Conclusion: The method of development adopted for the TAHK Framework has ensured it is both evidence and practice based, and further amendments and modifications are anticipated as new knowledge becomes available. The Framework will enable allied health clinicians to build on their existing capacities for KT, and approach this complex process in a rigorous and systematic manner. The TAHK Framework offers a unique focus on how knowledge is translated by allied health clinicians in multidisciplinary settings.